Stress in a hollow cylinder weakened by multiple crack-like defects - Stasyuk, B.M. (Reports of the National Academy of Sciences of Ukraine, 2021)
The three-dimensional stressed state of an elastic hollow cylinder, boundless along the axis containing multiple internal thin pliable inclusions is numerically modeled by a modified method of boundary integral equations. For this purpose, hypersingular integrals on the inclusion’s surfaces are presented in the form in which the behavior of the solution near their contours is implicitly taken into account. This modification allows us to unify the discretization of equations by the method of collocations and to directly determine the stress intensity factors on the contours of the inclusion’s midsurfaces. Numerical solutions of the problem of the interaction of two circular pliable inclusions are obtained. The irmidsurface lies in the same plane with the axis of the hollow cylinder, which is under the action of internal pressure.